7(x+1)=6x+12

Simple and best practice solution for 7(x+1)=6x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x+1)=6x+12 equation:



7(x+1)=6x+12
We move all terms to the left:
7(x+1)-(6x+12)=0
We multiply parentheses
7x-(6x+12)+7=0
We get rid of parentheses
7x-6x-12+7=0
We add all the numbers together, and all the variables
x-5=0
We move all terms containing x to the left, all other terms to the right
x=5

See similar equations:

| -5x+4=-80-8x | | 46+3x+62=93+47+4x | | 13x-13=2x+13 | | 2x+25=5x22 | | –6+8n=5n | | 3+x=63 | | s+612;s=7 | | -15m=4m+5 | | 2(-6d+5)=-4d+2* | | 12=-12t | | 5x+10=-5+40 | | 6h-5=11 | | P(x)=x4-12x2-64;x=4 | | 50=-7x | | 4=2p−2 | | 20g+-3g=34 | | 19=k/4+16 | | 5-2b=21 | | -.5x=4.3 | | 2x+53=7 | | 12x=19x= | | 17=r/4+16 | | 1/6+3x=-1/12 | | -6f-3f=-72 | | x=140+150+130 | | (5x6)+(3x)=36 | | −3(2x−4)+6x=12 | | 15=6x^2+6x+3 | | -6f3f=-72 | | 7(n−83)=91 | | -1=1/4(-m-19) | | 3(5+x)=9+9 |

Equations solver categories